In vitro and in vivo evaluation of macromolecular prodrug GC-FUA based nanoparticle for hepatocellular carcinoma chemotherapy - Can Huang; Na-Mei Li; Pei Gao; Sa Yang; Qian Ning; Wen Huang; Zhi-Ping Li; Peng-Ju Ye; Li Xiang; Dong-Xiu He; Xiang-Wen Tan; Cui-Yun Yu (Taylor & Francis Group, 2017)
A novel type of macromolecular prodrug delivery system is reported in this research. The N-galactosylated-chitosan-5-fluorouracil acetic acid conjugate (GC-FUA) based nanoparticle delivery system was evaluated in vitro and in vivo. Biocompatibility of GC-FUA-NPs was screened by BSA adsorption test and hemolysis activity examination in vitro. Cytotoxicity and cellular uptake study in HepG2 and A549 cells demonstrated that compared to free 5-Fu, the GC-FUA-NPs play great function in killing cancer cells for the cell endocytosis mediated by asialoglycoprotein receptor (ASGPR), which overexpresses on the cell surface. Pharmacokinetics study further illustrated that the drug-loaded nanoparticles has a much longer half-time than free 5-Fu in blood circulation in Sprague-Dawley (SD) rats. Tissue distribution was investigated in Kunming mice, and the result showed that the GC-FUA-NPs have a long circulation effect. The obtained data suggested that GC-FUA-NP is a very promising drug delivery system for efficient treatment of hepatocellular carcinoma.